Characterization of radial bending properties of cork (European Journal of Wood and Wood Products, 2011)
The behaviour of cork under three point bending stress in the radial direction was evaluated in relation to porosity (range 2.0–15.4%) and density (range 0.160– 0.220 g cm−3 ). The study was made using water-boiled cork planks of two commercial quality classes (good and poor quality) collected at an industrial mill. Cork samples were cut with the largest dimension in two directions, axial and tangential, and with the load zone in the inner part and the outer part of the plank. The stress-strain curves obtained in bending were similar for the different test specimens and similar to those observed for tensile tests in cork but the mechanical resistance of cork in bending was higher than in tension and lower than in compression. The direction of the internal stress in samples submitted to bending was a highly signiﬁcant factor of variation. The curves showed an initial linear elastic region with a mean Young’s modulus of 14 MPa for the tangential direction and 21 MPa for the axial direction, followed by a region of a gradual cork yielding up to a peak load, and failure at an average stress of 1.2 MPa and a strain of 14%. There was signiﬁcant difference in the bending properties of cork samples obtained from cork planks of different quality classes. Density and porosity were not individually well correlated with the mechanical parameters. It was however possible to model Young’s modulus by combining porosity and density.